Immune-metabolic interactions shape the fibrotic landscape of diabetic kidney disease: emerging mechanisms and therapeutic prospects - Gao, Yachan; Pang, Xinxin; Zhang, Huichao; Li, Dongdong; Han, Jiarui; Chen, Zhenyi; Chen, Xiaoyong; Li, Dongyang (Frontiers in Physiology, 2026)
Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease (ESRD), yet its progressive fibrosis cannot be solely attributed to hyperglycemia-induced oxidative stress or glomerular hypertension. Increasing evidence highlights that the bidirectional interaction between metabolic disturbances and immune activation—termed immunometabolic interactions—plays a pivotal role in driving DKD progression. Chronic metabolic stress, encompassing hyperglycemia, lipotoxicity, mitochondrial dysfunction, and gut-derived metabolites, reprograms innate and adaptive immune cells into pro-inflammatory and pro-fibrotic states. In turn, these activated immune cells exacerbate metabolic damage by promoting reactive oxygen species (ROS) overproduction, disrupting mitochondrial homeostasis, and facilitating extracellular matrix accumulation, thereby creating a self-amplifying loop that accelerates renal fibrosis. Key immunometabolic regulators, including HIF-1α, AMPK, mTOR, and SIRT1, coordinate metabolic signals with immune responses, providing novel mechanistic insights into DKD beyond traditional models. Recent therapeutic advances—such as Sodium-Glucose Cotransporter 2(SGLT2) inhibitors, GLP-1 receptor agonists, mineralocorticoid receptor antagonists, and multi-target natural compounds—offer renoprotective effects, partly by modulating these immunometabolic pathways. Fibrotic remodeling represents a core pathological tissue restructuring event in the kidney, typified by excessive extracellular matrix accumulation and irreversible structural destruction, which is coordinately propelled by the dual drivers of systemic metabolic disorders and local immune activation. A more precise characterization of immunometabolic alterations across disease stages, aided by single-cell and spatial multi-omics technologies, will be essential for identifying causal mechanisms rather than mere associations. Such discoveries could facilitate stage-specific, metabolism-immune–targeted interventions to prevent or slow fibrotic remodeling in DKD.